Overseas Medical Students in Ukraine and War-Related Interruption in Education: Global Health Considerations from India - Shubhajeet Roy; Vivek Bhat; Ahmad Ozair (Ubiquity Press, 2022)
Background: The Russian invasion of Ukraine in 2022 has caused a humanitarian crisis impacting millions of individuals within Ukraine and globally. While war-related healthcare delivery has been discussed in both the academic biomedical literature and in non-peer-reviewed sources, little academic attention has been paid to overseas medical students who have had to abandon their education. These constitute nearly a third of the 80,000 international students in Ukraine and represent a valuable part of the global healthcare workforce. Objective: This article utilizes the illustrative case of the over 18,000 Indian-origin medical students enrolled in Ukraine to review the state of overseas medical students in Ukraine and war-related interruption in education. Methods: Literature, both academic and non-academic, published up until October 1, 2022, pertaining to the conflict, the impact on students, the demands of various stakeholders, and the proposed solutions, was reviewed through the use of appropriate keyword-based searches. Findings: Factors influencing the decision to pursue education in Ukraine and their pre-crisis pathway to home practice are first discussed. Indian-origin students have historically gone on to Ukraine after securing insufficiently competitive ranks in the national medical school entrance exam, thus preventing them from getting a heavily subsidized education at publicly funded institutions in India. In the 2022 Russo-Ukrainian conflict, these students have faced not only actual and potential challenges related to their safety, shelter, food, and home return, they have been considerably impacted by the uncertainty regarding their educational prospects back home. The article then delineates the nuances and challenges in attempting to reintegrate a large potential healthcare workforce in the home country, and discusses possible solutions, especially those being implemented by the government. Conclusion: Urgent need exists for the involvement of all stakeholders and careful consensus-building before the proposed reintegration from an equity-based perspective.